If A and B are vector fields, prove the following:
∇.(A×B)=B⋅(∇×A)−A⋅(∇×B).
"\u2207\\cdot(A\u00d7B)=B\u22c5(\u2207\u00d7A)\u2212A\u22c5(\u2207\u00d7B)"
"A\u00d7B=\\begin{vmatrix}\n i & j &k\\\\\n A_x & A_y&A_z\\\\\n B_x & B_y&B_z\n\\end{vmatrix}=(A_yB_z-A_zB_y)i+(A_zB_x-A_xB_z)j+(A_xB_y-A_yB_x)k"
"\u2207\\cdot(A\u00d7B)=\\frac{\\partial}{\\partial x}(A_yB_z-A_zB_y)+\\frac{\\partial}{\\partial y}(A_zB_x-A_xB_z)+\\frac{\\partial}{\\partial z}(A_xB_y-A_yB_x)="
"=(\\frac{\\partial A_y}{\\partial x}-\\frac{\\partial A_x}{\\partial y})B_z+(\\frac{\\partial A_x}{\\partial z}-\\frac{\\partial A_z}{\\partial x})B_y+(\\frac{\\partial A_z}{\\partial y}-\\frac{\\partial A_y}{\\partial z})B_x-"
"-(\\frac{\\partial B_y}{\\partial x}-\\frac{\\partial B_x}{\\partial y})A_z-(\\frac{\\partial B_x}{\\partial z}-\\frac{\\partial B_z}{\\partial x})A_y-(\\frac{\\partial B_z}{\\partial y}-\\frac{\\partial B_y}{\\partial z})A_x="
"=B\u22c5(\u2207\u00d7A)\u2212A\u22c5(\u2207\u00d7B)"
Comments
Leave a comment